A physics conservation-based mesh patching algorithm for multi-body modeling and simulation - Song, Min; Li, Chao; Guo, Xiao-Wei; Zhang, Qing-Yang; Liu, Jie; Gao, Xiang (Computer aided design, 2026)
This paper introduces a physics-driven approach to improve fluid dynamics simulations of multi-body geometries with non-matching interfaces. Conventional methods often suffer from inaccuracies due to the lack of robust physical models. Our solution integrates Computational Fluid Dynamics (CFD) techniques and proposes a conservative interpolation algorithm that resolves interface mismatches without mesh modification. By using a dual-weighting scheme based on overlapping face areas, the algorithm ensures flux consistency across subdomains while maintaining high computational efficiency. Applicable to both structured and unstructured meshes, this simple yet robust method has been implemented in general-purpose CFD software and validated through complex cases. Specifically, in Couette flow between concentric cylinders, it shows a maximum 1.556% relative error in velocity distribution against analytical solutions, outperforming continuous mesh methods in accuracy. In reactor pressure vessel simulations, it achieves a pressure distribution error of 0.586% and a maximum flow distribution error of 1.645% compared to continuous mesh solutions. These results validate the method’s high accuracy and reliability in simulating diverse flow regimes, thus facilitating precise analyses for complex engineering problems. [Display omitted] •Developed physics-driven method for multi-body non-matching interfaces, ensuring conservation without mesh edits.•Robust algorithm works with structured/unstructured meshes via dual-weighting for efficiency and versatility.•Validated in complex reactor pressure vessel simulations with intricate multi-body geometries: 0.586% pressure error and 1.645% flow error vs. continuous meshes.•Enables FSI conjugate heat transfer for multi-body systems, preserving accuracy across non-matching interfaces while capturing fluid-solid thermal interactions.